Gambaran Perilaku Dalam Menyikat Gigi Terhadap Kejadian Abrasi Di Bagian Servikal Gigi Pada Lansia Di Posyandu Lansia Puskesmas Kejaksan - fikayuliani fikayuliani (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
Tooth abrasion is the mechanical erosion of teeth due to interaction with the instrument used. The significant horizontal use of the toothbrush also erodes tooth enamel. The general purpose of this study is to find out how the picture of brushing behavior at the posyandu for the elderly puskesmas Kejaksan. The specific objectives of this study are: (a) to determine brushing behavior in the elderly at the posyandu for the elderly at the Kejaksan Health Center. (b) to determine the incidence of tooth abrasion in the elderly at the posyandu for the elderly puskesmas Kejaksan. The data of this study was collected from 30 elderly people by means of interviews and direct examinations. This type of research is qualitative. The results of this study show that the behavioral picture in brushing teeth against the incidence of abrasion in the cervical part of the tooth in 2022 is: from 30 samples taken 22 people (73.3%) experienced abrasion events and did not have good enough knowledge about how to brush their teeth and as many as 8 people (26.7%) had good knowledge in brushing.